Porcelain Atrium: A Case Report with Literature Review - Krystle Leacock; Andre J. Duerinckx; Bonnie Davis (Case Reports in Radiology)
Massive left atrial wall calcification, or porcelain atrium, is very rare. We describe a case of an unusual pattern of cardiac calcification demonstrated on routine preoperative chest X-ray for cataract surgery in a 71-year-old Nigerian woman. Past medical history was significant for mitral stenosis and atrial fibrillation. Radiographic imaging revealed curvilinear high density areas of calcification outlining the left atrium on the chest X-ray. Noncontrast CT scan of the thorax confirmed the left atrial distribution of calcification and, thus, the diagnosis of porcelain left atrium.